Utilization of High-Power LEDs at Low-Cost Non-Invasive X-ray KV Meter Detectors Design - I, M. Bagus F.; P, Moch Prastawa A T; Setiawan, S Y; Lamidi, Lamidi; Hariwisana, I D G; Indrato, T B; Asghari, Mansour (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2022)
X-ray radiation is used to diagnose human body. In order to apply this method, two parameters are commonly used as the settings. The first is the KV value and the second is the mA value. In this case, when an error occurs in the kV setting, it will cause poor image quality, thus leads to inaccurate information in patient’s examination. It is likewise the presence of excessive doses to the patient's body. To ensure that the KV value produced is under the settings on the machine consul, both invasive and non-invasive measurements were carried out. Non-invasive is becoming an easy standard to do. Several types of equipment on the market and research results have been widely used for this non-invasive activity. The problem emerges is that the existing tools still use expensive detectors. The purpose of this study was to design a low-cost non-invasive x-ray KV meter detector using an LED detector whose ability was tested at each point of collimation. Furthermore, the method used in this study was to stump the detectors at 4 ends of the collimation by 20 cm apart. The data were taken by doing x-ray exposure at a distance of 60 cm. The module measurements were carried out under 80 mA exposure conditions for 1 second and a collimation area of ​​20 x 20 cm. Meanwhile, the x-ray exposure settings were performed at 40kV, 50kV, 60kV, and 70kV settings. The module measurement results were further compared to the x-ray machine setting values. Based on the comparison results, the smallest error rate was obtained on Sensor 2 by 0.83%, while the highest error rate was obtained on S5 by 6.43%. The results can be concluded that the LED phosphor can capture x-rays, but the detector was weak due to the interference from ambient light.